2016
DOI: 10.5469/neuroint.2016.11.2.78
|View full text |Cite
|
Sign up to set email alerts
|

Patient Radiation Exposure During Diagnostic and Therapeutic Procedures for Intracranial Aneurysms: A Multicenter Study

Abstract: PurposeTo assess patient radiation doses during cerebral angiography and embolization of intracranial aneurysms across multi-centers and propose a diagnostic reference level (DRL).Materials and MethodsWe studied a sample of 490 diagnostic and 371 therapeutic procedures for intracranial aneurysms, which were performed at 23 hospitals in Korea in 2015. Parameters including dose-area product (DAP), cumulative air kerma (CAK), fluoroscopic time and total angiographic image frames were obtained and analyzed.Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 19 publications
2
18
1
Order By: Relevance
“…For comparison, the dose of a routine CT examination of the abdomen is about 8–20 mSv, while the DAP for diagnostic cerebral angiography in patients with aneurysms is about 10,600 cGycm². 25 Image-guided therapy can be challenging in SMA patients and requires a high expertise as well as interdisciplinary cooperation between neurologists and neuroradiologists to successfully administer nusinersen and to minimise radiation exposure.…”
Section: Discussionmentioning
confidence: 99%
“…For comparison, the dose of a routine CT examination of the abdomen is about 8–20 mSv, while the DAP for diagnostic cerebral angiography in patients with aneurysms is about 10,600 cGycm². 25 Image-guided therapy can be challenging in SMA patients and requires a high expertise as well as interdisciplinary cooperation between neurologists and neuroradiologists to successfully administer nusinersen and to minimise radiation exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Ihn et al evaluated 371 aneurysm treatments nationwide in 2015 [ 25 ]. Total mean DAP, air kerma and fluoroscopy time were 219 Gycm 2 , 3.3 Gy and 51 min, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Direct measurement of the absolute entrance skin doses is not practicable and therefore surrogate markers such as DAP (Gycm 2 ) and air kerma (Gy) are usually used [23][24][25][26][27].…”
Section: Radiation Exposurementioning
confidence: 99%
“…[24] It was reported that the advantage of the rotational angiography in treating aneurysms provide a better understanding of the vasculature without the need for increased number of 2D image acquisitions compared to AVM interventions. [25] However, the number of 2D images acquired is at the discretion of the interventionists. Experienced interventionists with knowledge on radiation safety acquired 18% lower image frames during paediatric imaging compared to adults.…”
Section: Discussionmentioning
confidence: 99%